Identification of occupational risks: a case study in a cosmetics industry - Lira, Ana Clara Rocha; Pereira, Maria Eduarda Leite; Colvero, Diogo Appel (Brazilian Journal of Production Engineering, 2025)
Occupational safety has evolved in Brazil since the 20th century, driven by the need to protect workers, who faced precarious working conditions and frequent occupational accidents. Some significant milestones in this evolution include the creation of the Consolidation of Labor Laws (CLT) and the implementation of Regulatory Standards (NRs) starting in the 1970s. In this context, the adoption of tools such as risk maps and risk and prioritization matrices is of utmost importance. Thus, the aim of this study was to conduct a risk survey in the work environments of a cosmetics industry, evaluate the risks, and establish prioritization criteria for risk treatment. The methodology adopted was both qualitative and quantitative, collecting data comprehensively and on-site, and comparing them with the existing literature. The results showed a high degree of uniformity in risk perception, and the use of the risk matrix was essential for classifying the level of risk, where it was observed that there are no very high risks. The stages of developing the risk map and risk prioritization assessment involved the participation of workers, indicating that mental overload, high concentration levels, and fire should be prioritized.